Anticipated impact of the 2009 Four Corners raid and arrests - Goddard, Jennifer (2011)
Archaeological looting on United States federal land has been illegal for over a century. Regardless, the activity has continued in the Four Corners region. This paper discusses how the 1979 Archaeological Resources Protection Act (ARPA) can be viewed as sumptuary law, and within a sumptuary context, subversion can be anticipated. An analysis of 1986 and June 2009 federal raids in the Four Corners will exemplify this point by identifying local discourses found in newspapers both before and after each raid, which demonstrate a sumptuary effect. Ultimately, this paper concludes that looting just adapted, rather than halted, after each federal raid and that understanding this social context of continued local justification and validation of illegal digging is a potential asset for cultural resource protection.